Direct torque control of induction motor using a novel sliding mode control - Pham, Ngoc Thuy; Le, Duc Thuan; Nguyen, Phu Diep (International Journal of Power Electronics and Drive Systems (IJPEDS), 2025)
Direct torque control (DTC) for induction motor (IM) drive systems is recognized as a powerful control method known for its fast response and simple structure. However, this control method often suffers from several limitations, such as significant torque and current ripple, and sensitivity to variations in motor parameters. To address these issues, this paper proposes a novel sliding mode control strategy for the outer speed loop to improve the quality of DTC-based IM drive systems. Unlike previous approaches, we propose a novel adaptive parameter higher-order sliding mode (HOSM) controller for IM speed control. This approach enhances the drive system's performance by reducing torque ripple (a common issue in DTC), improving dynamic response, eliminating overshoot during transients, and increasing overall system stability. To ensure system stability, Lyapunov stability theory is used to design the control signals. The efficiency of the control law proposed in this paper is evaluated based on simulations performed on MATLAB-Simulink. The results obtained demonstrate that: First, the proposed control model for fast torque and speed responses, ensuring the drive system converges to the desired operating point during transients without encountering the phenomenon of exceeding the threshold. Second, the system maintains stable operation, even in the presence of load disturbances. Third, this method significantly reduces torque ripple, a common problem in IM drive systems using DTC techniques.